2020
DOI: 10.1016/j.ihj.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of oral paracetamol versus oral ibuprofen for patent ductus arteriosus closure in preterm neonates – A systematic review and meta-analysis

Abstract: Objective This systematic review and meta-analysis aimed to synthesize the latest evidence on the efficacy and safety of oral acetaminophen compared to oral ibuprofen for patent ductus arteriosus (PDA) in preterm infants. Methods We performed a systematic literature search on topics that assesses the use of oral paracetamol compared to oral ibuprofen in preterm neonates diagnosed with PDA from PubMed, EuropePMC, Cochrane Central Database, ScienceDirect, ProQuest, Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Acetaminophen has been also shown to be effective in closing the ductus within 48 hours that was refractory to ibuprofen 21 . A recent meta‐analysis revealed that oral acetaminophen to be superior to oral ibuprofen in neonates <34 weeks of gestational age (OR: 1.73; 95% CI: 1.01, 2.94) 22 . We did not observe any significant association between post‐natal days of treatment while a recent study, although not statistically significant, observed that 80% success rate for ≤7 days compared to 68% afterwards 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen has been also shown to be effective in closing the ductus within 48 hours that was refractory to ibuprofen 21 . A recent meta‐analysis revealed that oral acetaminophen to be superior to oral ibuprofen in neonates <34 weeks of gestational age (OR: 1.73; 95% CI: 1.01, 2.94) 22 . We did not observe any significant association between post‐natal days of treatment while a recent study, although not statistically significant, observed that 80% success rate for ≤7 days compared to 68% afterwards 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it could be argued that this knowledge gap has allowed us to perform and publish clinical studies without including relevant short-and long-term pulmonary outcomes while planning and publishing systematic reviews without considering relevant pulmonary outcomes. 90,91 Clinical Studies: Potential Signals for Harm APAP use during pregnancy is considered safe due to a lack of reported adverse effects, rather than data from preclinical models and clinical trials demonstrating safety. 92 Safety during pregnancy is so accepted that exposures now occur in 50%-60% of pregnancies in the US, Europe, and Australia.…”
Section: Pulmonary Cyp2e1 Expression: Developmentally Regulated and Clinically Relevantmentioning
confidence: 99%
“…Five meta-analyses have been published. 14,91,[130][131][132] The most recent meta-analysis, comparing oral (PO) APAP with PO ibuprofen, did not report BPD in their outcomes. 91 In the remaining 4 studies, there was no signal for increased BPD in subjects exposed to APAP.…”
Section: Nicu Exposures: Underpowered To Determine Safety and Detect Harm Not Reassuringmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The last decade there has been a great interest in the use of paracetamol as an alternative pharmacological agent, which is a less potent inhibitor of the peripheral cyclo-oxygenase cycle and seems to exerts its mode of action mainly through central nervous system receptors and, therefore has a better safety profile when compared to NSAIDs. 6,10 We conducted a systematic review and meta-analysis (SRMA) of randomized controlled trials (RCTs) to investigate the safety and efficacy of paracetamol versus NSAIDs in neonates with PDA. We included RCTs only in an attempt to strengthen the level of evidence of the results.…”
mentioning
confidence: 99%